The Influence of Operating Cash Flows and Receivables Towards Current Ratios in Multifinance Companies in Indonesia Stock Exchange (Bei) 2013-2017 Periode - Ayke Nuraliati; Dwiutomo Bhakti (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
This study aims to determine the effect of Operating Cash Flow and Accounts Receivable Turnover on the company's ability to pay off short-term liabilities (liquidity) using the Current Ratio method for Multifinance Companies on the Indonesia Stock Exchange Period 2013-2017 The research method used is descriptive method and verification method with a quantitative approach. The data used are secondary data in the form of financial statements of multi-finance companies for the period 2013-2017. The design of hypothesis testing uses starting from the classical assumption test, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis and t test.The results showed that the Operating Cash Flow and Accounts Receivable Turnover influence the Current Ratio.